A baseline assessment of the photosynthetic potential of Welwitschia mirabilis using the JIP-test for monitoring and conservation purposes - Berner, J.M.; Cloete, H.; Shuuya, T. (African Biodiversity & Conservation, 2021)
Background: Welwitschia mirabilis is highly specialised to survive the harsh climate of the Namib Desert. Changes in land use, such as the expansion of mining activities, may endanger their survival.Objectives: The purpose of this study was to understand the photosynthetic potential of W. mirabilis plants to provide a baseline for future long-term monitoring, and for future comparison to determine plant health status after the onset of mining operations.Methods: The study was conducted in a population of W. mirabilis on the Welwitschia Plains. Chlorophyll a fluorescence data were used to measure plant photochemical potential and analysed using the JIP-test.Results: Significant differences in the photosynthetic potential was observed for W. mirabilis plants located in different catchments. The partial parameters of the PIABS values were also significantly lower, which indicated that all aspects of photosynthesis were influenced.Conclusion: PIABS values can serve as a baseline for future long-term monitoring studies to detect any changes in the health status of W. mirabilis that might result from land use change.